Preliminary tolerance analysis of adjuvant chemotherapy in older patients after resection of stage III colon cancer from the PRODIGE 34-FFCD randomized trial. Issue 4 (April 2023) - Aparicio, Thomas; Bouché, Olivier; Etienne, Pierre-Luc; Barbier, Emilie; Mineur, Laurent; Desgrippes, Romain; Guérin-Meyer, Véronique; Hocine, Fayçal; Martin, Jean; Le Brun-Ly, Valérie; Cretin, Jacques; Desramé, Jérôme; et al.
Abstract: Background: Colon adenocarcinoma mainly occurs in older patients. Oxaliplatin-based adjuvant chemotherapy improved disease-free survival after stage III colon cancer resection, but this improvement was not demonstrated in older patients. Methods: The purpose of ADAGE-PRODIGE 34, randomized open phase III trial is to compare in patients over 70 years oxaliplatin plus fluoropyrimidine with fluoropyrimidine alone in fit patients (Group 1) and fluoropyrimidine with observation in frail patients (Group 2) after resection of stage III colon adenocarcinoma. We report a preliminary tolerance analysis on 50% of the first patients enrolled. Results: The analysis was conducted on 491 patients (378 in Group 1 and 113 in Group 2). Patients in Group 2 were older and showed more frailty criteria than those in Group 1. Cumulative grade 3–5 toxicities were more frequent in patients treated with oxaliplatin in Group 1 or with fluoropyrimidine in Group 2 than in patients treated with fluoropyrimidine in Group 1. At least one course was deferred in more than half of the patients in all groups. Early treatment cessation was more frequent in Group 2. Conclusion: No safety concerns were raised for the continuation of accrual. The frailty criteria distribution suggests that the investigator's evaluation for group allocation was accurate.